ARTIFICIAL INTELLIGENCE IN EDUCATION: TRANSFORMING PEDAGOGY AND LEARNING PARADIGMS (Uzbekistan Open Conference, 2025)
This article is dedicated to that Artificial Intelligence (AI) has emerged as a transformative force across multiple sectors, and education is among the fields most profoundly affected. This paper examines the evolving role of AI in educational contexts, emphasizing its applications in personalized learning, assessment, and institutional management. It also addresses the ethical challenges associated with AI deployment, including data privacy, bias, and equitable access.